Challenges in the Use of Artificial Intelligence-enabled Systems in Modern Armed Forces - Prezelj, Iztok (European Integration Studies, 2024)
The application of Artificial Intelligence (AI) in the armed forces brings about a number of new possibilities and also new risks. In this paper, we have identified and analysed a wide range of risks associated with uncontrolled and unstoppable development of general AI, as well as several ethical and legal, operational and strategic risks. We have shown how and why these risks are dangerous and some even pose a threat to human security, values, norms, democracy, human rights, etc. These risks need to be carefully examined in order to improve the military use of AI and regulation in this area. The wide range of risks identified and their extremely diverse nature show that regulating the military use of AI will be difficult and complex, requiring all disciplines of law, and that regulatory rules need to be applied at national, regional and global level. The rapid development of military AI suggests that some risks are likely to be considered and regulated before any malicious military use of AI occurs, while unfortunately some others will only be regulated after the first instances of its malicious and illegal use by some armed forces.